Flettner Rotor Modification through Adding Ridges and Fins with Results Comparison to Base Model - Nowar Deeb; Achmad Baidowi; Adi Kurniawan (International Journal of Marine Engineering Innovation and Research, 2023)
Oceans are the most crucial factor in maintaining global environmental equilibrium. Researchers are looking into the possibility of capturing wind power for shipping. Ship builders and owners provide several solutions based on the use of electrical power, low-polluting fuels, solar energy, and wind energy. The goal of this research is to learn more about using Flettner rotors as alternate sources of power and to create a new operational model for the rotor that could generate more power output from the currently available base model. Due to the sluggish market and glut of tonnage, the global shipping industry is now having difficulties. Only a few ships have wind-assisted technologies to help them save money on fuel. For the research, we created a base model in the 3D program from the available data about the commercially used Flettner rotor, then we modified a number of variations for the model and compared the results we reached from the CFD software to find an outcome that is better than the current output of the base model, and the results have shown improvement for the lower wind speeds.